2019
DOI: 10.1002/cncr.32293
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer subtypes among Eastern‐African–born black women and other black women in the United States

Abstract: BACKGROUND:A previous study reported that Eastern-African-born black women in the United States had lower prevalence of estrogen receptor-negative breast cancer than those in US-born and Western-African-born black women, among whom the prevalence was similar. It is unknown whether the prevalence of triple-negative breast cancer (negative for estrogen receptor, progesterone receptor, and human epidermal growth factor 2 receptor) among black women in the United States differs similarly by birthplace. METHODS: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 38 publications
2
31
0
1
Order By: Relevance
“…For example, a recent study reported that the prevalence of the triple-negative subtype in black women in the United States varied substantially by country of birth; compared with US-born blacks, the prevalence was 47% lower in women born in countries in Eastern Africa but only 8% lower in Western Africa-born blacks. 21 In another study of women in California, those of Korean, Filipina, Chinese, and Southeast Asian descent had a higher risk of HER2-positive breast cancers compared with white women, whereas those of Japanese and Asian Indian descent had a lower risk. 22 Differences in breast cancer subtype within and between racial/ethnic groups likely reflect variations in the prevalence of breast cancer risk factors 23 and mammography use, 24 but may also be related to genetic variations.…”
Section: Cancer Occurrence In the Most Recent Time Periodmentioning
confidence: 98%
See 3 more Smart Citations
“…For example, a recent study reported that the prevalence of the triple-negative subtype in black women in the United States varied substantially by country of birth; compared with US-born blacks, the prevalence was 47% lower in women born in countries in Eastern Africa but only 8% lower in Western Africa-born blacks. 21 In another study of women in California, those of Korean, Filipina, Chinese, and Southeast Asian descent had a higher risk of HER2-positive breast cancers compared with white women, whereas those of Japanese and Asian Indian descent had a lower risk. 22 Differences in breast cancer subtype within and between racial/ethnic groups likely reflect variations in the prevalence of breast cancer risk factors 23 and mammography use, 24 but may also be related to genetic variations.…”
Section: Cancer Occurrence In the Most Recent Time Periodmentioning
confidence: 98%
“…Importantly, studies suggest that the distribution of breast cancer subtypes varies within broadly defined racial/ethnic groups. For example, a recent study reported that the prevalence of the triple‐negative subtype in black women in the United States varied substantially by country of birth; compared with US‐born blacks, the prevalence was 47% lower in women born in countries in Eastern Africa but only 8% lower in Western Africa‐born blacks . In another study of women in California, those of Korean, Filipina, Chinese, and Southeast Asian descent had a higher risk of HER2‐positive breast cancers compared with white women, whereas those of Japanese and Asian Indian descent had a lower risk .…”
Section: Selected Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…NHBs have a high prevalence of the very aggressive and clinically challenging BCa subtype called triple‐negative breast cancer (TNBC), which is characterized by the absence of 3 therapeutically relevant BCa biomarkers: estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) . Currently, TNBC patients are treated with a combination of nontargeted chemotherapies, radiotherapy, and surgery .…”
Section: Introductionmentioning
confidence: 99%